Sigma-1 receptor concentration in plasma of patients with late-life depression: a preliminary study - Shimizu H (Dove Medical Press, 2013)
Hideyuki Shimizu,1 Minoru Takebayashi,2 Masayuki Tani,1 Hiroaki Tanaka,1 Bun Yamagata,1 Kenzo Kurosawa,1 Hiroki Yamada,1 Mitsugu Hachisu,3 Kazue Hisaoka-Nakashima,2 Mami Okada-Tsuchioka,2 Masaru Mimura,4 Akira Iwanami11Department of Neuropsychiatry, Showa University School of Medicine, Tokyo, Japan; 2Department of Psychiatry and Institute for Clinical Research, National Hospital Organization Kure Medical Center, Kure, Japan; 3Department of Clinical Psychopharmacy, Pharmacy School, Showa University, Tokyo, Japan; 4Department of Neuropsychiatry, Keio University School of Medicine, Tokyo, JapanBackground: Recently, the sigma-1 receptor has been shown to play a significant role in the neural transmission of mood by regulating N-methyl-D-aspartate receptors. Additionally, the sigma-1 receptor has been reported to influence cognitive functions including learning and memory. In this study, we measured plasma sigma-1 receptor concentrations before and after antidepressant treatment in patients with late-life major depressive disorder (MDD) and explored whether changes in depressive status are related to sigma-1 receptor concentrations.Methods: The study participants were 12 subjects with late-life MDD diagnosed according to the criteria of the Diagnostic and Statistical Manual of Mental Disorders, Fourth Edition. All of the participants were over 60 years old. Immediately prior to and 8 weeks after the start of treatment, sigma-1 receptor concentration and mental status, including depressive symptoms (Hamilton Depression Rating Scale; HAM-D), were measured. Treatment for depression was performed according to a developed algorithm based on the choice of treatments. We examined the association between changes in sigma-1 receptor concentration and HAM-D scores during antidepressant treatment. For the measurement of plasma sigma-1 receptor concentration, blood plasma samples were separated by sodium dodecyl sulfate polyacrylamide gel electrophoresis. Western blots were performed using a specific antibody that acts against the sigma-1 receptor, and the net densities of each band were quantified.Results: All participants showed improvement in depressive symptoms, which was indicated by a significant decrease in the HAM-D scores. The mean plasma sigma-1 receptor concentration also increased significantly following antidepressant treatment. However, no significant correlations were found between changes in plasma sigma-1 receptor concentration and changes in HAM-D scores.Conclusion: In this preliminary study, we demonstrated that the sigma-1 receptor concentration in plasma increases following antidepressant treatment in patients with late-life MDD. Further studies are warranted to confirm this finding with a larger number of patients.Keywords: sigma-1 receptor, late-life depression, depressive symptoms, antidepressant treatment